2008
DOI: 10.1080/02699200801919745
|View full text |Cite
|
Sign up to set email alerts
|

The co‐development of speech and gesture in children with autism

Abstract: Recent interest in gesture has led to an understanding of the development of gesture and speech in typically developing young children. Research suggests that initially gesture and speech form two independent systems which combine together temporally and semantically before children enter the two-word period of language development. However, little is known about gesture development in children's disordered speech. This paper presents two case studies of young children with autism. The children are under 3 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 13 publications
2
18
0
1
Order By: Relevance
“…However, very little is known about whether children with ASDs integrate speech and gesture in their speech production. Recently, Sowden et al (2008Sowden et al ( , 2013 conducted two case studies on this question. One study examined the gestures produced by two 2-yearold children with ASDs who had attended an intensive intervention program on social and communicative skills (Sowden et al, 2008).…”
Section: Gesture Development In Children With Autism Spectrum Disordersmentioning
confidence: 99%
See 4 more Smart Citations
“…However, very little is known about whether children with ASDs integrate speech and gesture in their speech production. Recently, Sowden et al (2008Sowden et al ( , 2013 conducted two case studies on this question. One study examined the gestures produced by two 2-yearold children with ASDs who had attended an intensive intervention program on social and communicative skills (Sowden et al, 2008).…”
Section: Gesture Development In Children With Autism Spectrum Disordersmentioning
confidence: 99%
“…Recently, Sowden et al (2008Sowden et al ( , 2013 conducted two case studies on this question. One study examined the gestures produced by two 2-yearold children with ASDs who had attended an intensive intervention program on social and communicative skills (Sowden et al, 2008). They found that after training, only one child produced reinforcing gestures (but not supplementary or disambiguating gestures).…”
Section: Gesture Development In Children With Autism Spectrum Disordersmentioning
confidence: 99%
See 3 more Smart Citations